2007
DOI: 10.1017/s0022215107005683
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prognostic factors on recovery from sudden hearing loss

Abstract: The outcome of sudden hearing loss was unaffected by systemic disease, tinnitus or type of audiogram (except for midfrequency type). The following were poor prognostic factors in the outcome of sudden hearing loss: female gender, presence of vertigo, initiation of treatment more than seven days after onset of hearing loss, and >40 dB hearing loss on admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
77
6
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 42 publications
9
77
6
2
Order By: Relevance
“…have been suggested. Some studies have reported that the female gender was suggested to be poor prognostic factor for recovery of hearing loss (Ceylan et al, 2007) and male gender was related to better hearing outcomes (Xenellis J et al, 2006). In our study, correlation between gender and prognosis for recovery of hearing loss was not evident.…”
Section: Fig 3 Decision Tree Model Of Important Variables As Prognocontrasting
confidence: 67%
See 2 more Smart Citations
“…have been suggested. Some studies have reported that the female gender was suggested to be poor prognostic factor for recovery of hearing loss (Ceylan et al, 2007) and male gender was related to better hearing outcomes (Xenellis J et al, 2006). In our study, correlation between gender and prognosis for recovery of hearing loss was not evident.…”
Section: Fig 3 Decision Tree Model Of Important Variables As Prognocontrasting
confidence: 67%
“…Many studies regarded the severity of hearing loss is one of the important prognostic factors for improvement of ISSHL (Byl FM., 1984;Fetterman BL et al, 1999;Psifidis AD et al, 2006;Cvorovic L et al, 2008;Ceylan A et al, 2007) However, the standard of severity which could affect the prognosis, was different in each study Moreover, some studies have reported that the initial hearing level had no statistical point on prognosis (Suzuki H et al, 2011;Wang L et al, 2009). In our study, there was no difference in severity of hearing loss between improvement and no improvement groups.…”
Section: Fig 3 Decision Tree Model Of Important Variables As Prognomentioning
confidence: 99%
See 1 more Smart Citation
“…This uncertainty leads to the investigation of efficacy of commonly used agents, particularly systemic steroids. The randomized controlled study by Wilson et al (2) in 1980 is known as a milestone in SHL treatment as high dose systemic steroid therapy, either oral, intravenous or parenteral, has been considered standard therapy (13). Although the exact mechanism is unknown, corticosteroids are thought to improve hearing loss by suppressing immune response, improving the decreased microcirculation, and reducing inflammation, edema and endolymphatic pressure in inner ear (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…As the majority of patients have idiopathic SSNHL, treatment options also depend on hypotheses. Steroids, rheological agents, vasodilators, antiviral agents, vitamin-electrolyte complexes, anticoagulants and hyperbaric oxygen therapy are being used for SSNHL in form of "gun-shot" therapy (3,10,(13)(14)(15)(16).…”
mentioning
confidence: 99%